Basic anaesthesia handbook - Nadia Hanom Ishak (UiTM Press, 2015)
Basic Anaesthesia Handbook is a core anaesthesia knowledge packed in a nutshell for a quick grasp and fast read on the important facts of perioperative anaesthesia management primarily designed for medical students. It also provides a concise and comprehensive knowledge in basic principles of anaesthesia for doctors who are in their early exposure of the specialty and those who intend to pursue this field as their future professional career. The contents of the handbook are clearly highlighted in point forms and reinforced with diagrams, figures, graphs, tables, flow charts and mnemonics. Description of the subjects is presented in a systematic manner using simple language that is easily understood. This handbook serves as one of the references in anaesthesia, hence prior basic knowledge on anatomy, physiology and pharmacology are still essential to appreciate the true beauty of anaesthesia